Pengabdian Hukum Gratis Sukseskan Aktualisasi Off Class Paralegal Asal Desa Meteseh, Kendal, Jawa Tengah - Joko Susanto; Abdul Aziz; Sisyanto, Sisyanto (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
Actualization of the role of off-class paralegals in the Meteseh Village area, Boja District, Kendal Regency, Central Java Province, shows a significant contribution in increasing access to justice for rural communities. The author who acts as a paralegal has succeeded in holding various community service activities, such as free legal counseling for students to improve their understanding of legal rights and obligations. Holding free legal consultation activities for people who face daily legal problems, so that people can get solutions without cost, aka free. Furthermore, paralegals also play a role in non-litigation assistance for the revocation of change of address files, as well as helping to complete aspects of legal administration, namely helping to draft inheritance statements and sale and purchase agreements, as well as acting as witnesses in the process of making these documents. This activity proves that off-class paralegals not only play a role as legal assistants, but also as agents of social change that strengthen legal awareness in rural communities. By using a qualitative approach with the Participatory Action Research (PAR) method, which emphasizes the active involvement of research subjects in the process of identifying, analyzing, and resolving legal problems in the community, this program creates an effective and sustainable legal empowerment model. This success confirms that the existence of paralegals in Meteseh Village can be a solution to the limited access of the community to professional legal services.